Researching moral distress among New Zealand nurses: A national survey - Woods, Martin (Nursing ethics, 2015)
Background:Moral distress has been described as a major problem for the nursing profession, and in recent years, a considerable amount of research has been undertaken to examine its causes and effects. However, few research projects have been performed that examined the moral distress of an entire nation’s nurses, as this particular study does.Aim/objective:The purpose of this study was to determine the frequency and intensity of moral distress experienced by registered nurses in New Zealand.Research design:The research involved the use of a mainly quantitative approach supported by a slightly modified version of a survey based on the Moral Distress Scale–Revised.Participants and research context:In total, 1500 questionnaires were sent out at random to nurses working in general areas around New Zealand and 412 were returned, giving an adequate response rate of 27%.Ethical considerations:The project was evaluated and judged to be low risk and recorded as such on 22 February 2011 via the auspices of the Massey University Human Ethics Committee.Findings:Results indicate that the most frequent situations to cause nursing distress were (a) having to provide less than optimal care due to management decisions, (b) seeing patient care suffer due to lack of provider continuity and (c) working with others who are less than competent. The most distressing experiences resulted from (a) working with others who are unsafe or incompetent, (b) witnessing diminished care due to poor communication and (c) watching patients suffer due to a lack of provider continuity. Of the respondents, 48% reported having considered leaving their position due to the moral distress.Conclusion:The results imply that moral distress in nursing remains a highly significant and pertinent issue that requires greater consideration by health service managers, policymakers and nurse educators.